Waterproof powder-blocking-free pressed powder and preparation method thereof
By combining plant extracts and modified locust bean gum silane prepolymers, the combination of silica hybrid corn starch, aminoporous corn starch and stearic acid-tannin hybrid mica powder, the Existing waterproof powder cakes may cause pore blockage and powder stagnation, achieving excellent waterproofness, oil control and makeup control and stability.
Patent Information
- Application Number
- CN202411774598.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing waterproof powder cakes may cause blockage of pores after long-term use, and may cause people with dry skin or fine lines to become prone to powder stuck.
Using the combination technology of silica hybrid corn starch, aminolated porous corn starch and stearic acid-tannin hybrid mica powder, combined with plant extracts and modified locust bean gum silane prepolymer, the formation is good Hydrophobic and bondable powder.
It realizes excellent waterproofness, oil-controlled makeup and skin feeling of the powder, while avoiding powder trapping, and improving the powder resistance to powder removal and stability under high and low temperature cycles.
Smart Images

Figure BDA0005171097580000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cosmetics, and particularly relates to a waterproof and non-sticky pressed powder and a preparation method thereof. Background Art
[0002] Pressed powder is a base makeup product that can control oil, cover blemishes, and modify pores. It is a cake-shaped solid made by mixing and pressing a variety of powder raw materials (including pigments) and adhesives (oil components). In summer, due to the hot weather, sweat and oil secretion are more, so pressed powder needs to have a certain degree of waterproofness. In the prior art, the Chinese patent with the authorization publication number of CN 115363967 B discloses a waterproof, sweat-proof, long-lasting makeup and skin care pressed powder and its preparation method. The waterproof, sweat-proof and long-lasting makeup and skin care powder comprises a coating structure I and a coating structure II; the coating structure I comprises a core material layer I and an inner coating layer I from the inside to the outside in sequence; the core material layer I comprises talcum powder UNI-Talc2500FL and a colorant; the inner coating layer I comprises petrolatum, acrylic acid (ester) / ethylhexyl acrylate / polydimethylsiloxane methacrylate copolymer; the coating structure II comprises a core material layer II and an inner coating layer II from the inside to the outside in sequence; the core material layer II comprises a colorant Ti-AL 1765AS and nylon-12; the inner coating layer II comprises petrolatum, acrylic acid (ester) / ethylhexyl acrylate / polydimethylsiloxane methacrylate copolymer. Due to the special structures of the coating structure I and the coating structure II, the powder has a good waterproof and sweat-proof effect. However, the talcum powder of this technical solution has a strong adsorption capacity, and long-term use may cause pore blockage. At the same time, this technical solution adds a large amount of hydrophobic talc, which makes it easy for people with dry skin or fine lines to experience powder sticking.
[0003] Therefore, it is of great significance to provide a waterproof and non-sticky pressed powder. Summary of the invention
[0004] In view of the above problems, the present invention provides a waterproof and non-sticky pressed powder and a preparation method thereof. The waterproof and non-sticky pressed powder has excellent water resistance, skin feel and stability.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] The first aspect of the present invention provides a waterproof and non-sticky powder cake, wherein the raw materials include, by weight, 30-60 parts of powder, 2-5 parts of plant extract, 4-8 parts of locust bean gum silane prepolymer, 3-6 parts of film former, 2-5 parts of emollient, and 2-4 parts of phytic acid;
[0007] The powder is a mixture of silicon dioxide hybrid corn starch, amino porous corn starch and stearic acid-tannic acid hybrid mica powder; the mass ratio of the silicon dioxide hybrid corn starch, amino porous corn starch and stearic acid-tannic acid hybrid mica powder is 1: (10-25): (5-10).
[0008] Preferably, the mass ratio of the silicon dioxide hybrid corn starch, the amino porous corn starch and the stearic acid-tannic acid hybrid mica powder is 1:20:8.
[0009] Preferably, the method for preparing the silicon dioxide hybridized corn starch comprises the following steps:
[0010] S1. dissolving waxy corn starch in a phosphate buffer, heating and stirring to completely gelatinize the starch to obtain a starch solution; cooling the starch solution, adding pullulanase to debranch the starch solution, centrifuging the solution after debranching, removing the precipitate, boiling the supernatant to inactivate the pullulanase, and centrifuging the solution again to obtain a debranched starch solution; retrograding the debranched starch solution, centrifuging the solution after retrogradation to obtain a precipitate; washing and drying the precipitate to obtain nano-resistant corn starch;
[0011] S2. Place nano-resistant corn starch in ethanol, add tetraethyl orthosilicate and water to react, add ammonia water dropwise during the reaction to adjust the pH to 10.5-11.5, and wash and dry the product after the reaction.
[0012] Further preferably, the method for preparing the silicon dioxide hybridized corn starch comprises the following steps:
[0013] S1. dissolving waxy corn starch in phosphate buffer, stirring at 100° C. for 30-50 min to completely gelatinize it, and obtaining a starch solution; cooling the starch solution to 58° C., adding pullulanase for debranching for 7-9 h, centrifuging at 3000-4000 rpm for 1 min after debranching, removing the precipitate, boiling the supernatant to inactivate the pullulanase, and centrifuging at 3000-4000 rpm for 1 min to obtain a debranched starch solution; reversing the debranched starch solution at 50° C. for 10-12 h, and centrifuging at 3000-4000 rpm for 8-15 min after reversing to obtain a precipitate; washing and drying the precipitate to obtain nano-resistant corn starch;
[0014] S2. Place nano-resistant corn starch in ethanol, add ethyl orthosilicate and water to react at 70-90°C for 3-6 hours, add ammonia water dropwise during the reaction to adjust the pH to 10.5-11.5, and wash and dry the product after the reaction.
[0015] Preferably, the ratio of the waxy corn starch to the phosphate buffer is 1 g:10 mL.
[0016] Preferably, the pullulanase is added in an amount of 30-50 u / g waxy corn starch.
[0017] Preferably, the mass ratio of the nano-resistant corn starch, ethanol, tetraethyl orthosilicate and water is 1:
[0018] (60-80):(4-8):(3-5).
[0019] Preferably, the method for preparing the aminated porous corn starch comprises the following steps: placing the porous corn starch in an ethanol aqueous solution, adding γ-aminopropyltriethoxysilane to react, and filtering, washing and drying after the reaction is completed.
[0020] Further preferably, the preparation method of the amino porous corn starch specifically comprises the following steps: placing the porous corn starch in an ethanol aqueous solution, adding γ-aminopropyltriethoxysilane to react at 70-80°C for 6-10h, filtering, washing and drying after the reaction is completed.
[0021] Preferably, the mass ratio of the porous corn starch, the ethanol aqueous solution and γ-aminopropyltriethoxysilane is 1:(5-8):(0.05-0.15).
[0022] Preferably, the ethanol aqueous solution is a mixture of ethanol and water in a mass ratio of (4-6):1.
[0023] Preferably, the method for preparing the stearic acid-tannic acid hybrid mica powder comprises the following steps:
[0024] (1) placing tannic acid and mica powder in water for reaction, centrifuging, washing, and drying after the reaction to obtain tannic acid hybrid mica powder;
[0025] (2) Mix tannic acid hybrid mica powder, stearic acid and ethanol to react, centrifuge, wash and dry after the reaction is completed.
[0026] Further preferably, the method for preparing the stearic acid-tannic acid hybrid mica powder comprises the following steps:
[0027] (1) placing tannic acid and mica powder in water at 75-85° C. for reaction for 2-3 hours, centrifuging, washing, and drying after the reaction to obtain tannic acid hybrid mica powder;
[0028] (2) Mix tannic acid hybrid mica powder, stearic acid and ethanol at 75-85° C. and react for 1-2 hours. After the reaction, centrifuge, wash and dry to obtain the product.
[0029] Preferably, the D90 of the mica powder is 2-4 μm, preferably 3 μm.
[0030] Preferably, the mass ratio of tannic acid, mica powder and water is (8-12):1:(80-120).
[0031] Preferably, the mass ratio of the tannic acid hybrid mica powder, stearic acid and ethanol is 1:(0.05-0.15):(8-12).
[0032] The present invention creatively prepares silica hybrid corn starch, aminated porous corn starch and stearic acid-tannic acid hybrid mica powder, wherein the silica hybrid corn starch is silica hybrid nano-resistant corn starch, the aminated porous corn starch is porous corn starch modified by a silane coupling agent containing amino groups, and the stearic acid-tannic acid hybrid mica powder has a core-shell structure with stearic acid-tannic acid as an outer shell and mica powder as an inner core; by adopting the above technical scheme, the powder has good hydrophobicity and good water resistance, and at the same time has excellent oil control and makeup retention, and matte soft focus properties even without using talcum powder; in addition, the inventors unexpectedly discovered that the silica hybrid corn starch is a silica hybrid nano-resistant corn starch, the aminated porous corn starch is a porous corn starch modified by a silane coupling agent containing amino groups, and the stearic acid-tannic acid hybrid mica powder has a core-shell structure with stearic acid-tannic acid as an outer shell and mica powder as an inner core; by adopting the above technical scheme, the powder has good hydrophobicity and good water resistance, and at the same time has excellent oil control and makeup retention, and matte soft focus properties even without using talcum powder; in addition, the inventors also unexpectedly discovered that the silica hybrid corn starch is a silica hybrid nano-resistant corn starch, the aminated porous corn starch is a porous corn starch modified by a silane coupling agent containing amino groups, and the stearic acid-tannic acid hybrid mica powder has a core-shell structure with stearic acid-tannic acid as an outer shell and mica powder as an inner core; by adopting the above technical scheme, the powder has good hydrophobicity and water resistance, and at the same time has excellent oil control and makeup retention, and matte soft focus properties even without using talcum powder; in addition, the inventors also unexpectedly discovered that the silica hybrid corn starch is a silica hybrid nano-resistant corn starch, The compound use of silica hybrid corn starch, amino porous corn starch and stearic acid-tannic acid hybrid mica powder also improves the powder cake's resistance to powder flying and stability under high and low temperature cycles. It is speculated that this is because the powder is prone to generate static electricity during the powder collection process, resulting in particle scattering, and their compound use can reduce the static electricity effect, thereby reducing the powder flying phenomenon. In addition, the amino groups on the surface of the amino porous corn starch form phytate with the phytic acid in the system. The presence of phytate further improves the antistatic properties of the powder cake, reduces powder flying, and can make the powder particles more closely combined together, reducing the separation and shedding of particles when the temperature changes.
[0033] Preferably, the plant extract is a mixture of chicory root extract, phytosphingosine and Gynostemma pentaphyllum extract, and the mass ratio of the chicory root extract, phytosphingosine and Gynostemma pentaphyllum extract is (4-8):1:(2-4).
[0034] A problem that bothers consumers with waterproof, oil-control and long-lasting powder is the poor fit of the powder, which is prone to powder sticking. The inventors have found that by adding plant extracts to the system of the present invention, when the plant extract is a mixture of chicory root extract, phytosphingosine and Gynostemma pentaphyllum extract, and mixed with powder, locust bean gum silane prepolymer and phytic acid, the components cooperate with each other, which can improve the fit of the powder while maintaining waterproof, oil-control and long-lasting makeup, and avoid the powder sticking phenomenon.
[0035] Preferably, the method for preparing the locust bean gum silane prepolymer comprises the following steps: placing locust bean gum in water, stirring, adding potassium hydroxide, and dripping 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane to react to obtain the prepolymer.
[0036] Further preferably, the preparation method of the locust bean gum silane prepolymer comprises the following steps: placing locust bean gum in water, stirring at 70-85° C. for 20-40 min, adding potassium hydroxide, and dripping 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane to react at 85-95° C. for 2-5 h to obtain the prepolymer.
[0037] Preferably, the mass ratio of locust bean gum, water, potassium hydroxide and 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane is 10:(15-25):(0.1-0.3):(3-5).
[0038] Preferably, the mass ratio of the powder, the plant extract, the locust bean gum silane prepolymer and the phytic acid is (14-16):(1-2):(1.5-2.5):1.
[0039] In order to improve the stability of pressed powder under various conditions, the inventors creatively used 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane to modify locust bean gum. The modified locust bean gum has a higher adhesion to the powder and other ingredients, forming a more stable composite structure, which can reduce the possibility of cracking and falling off, thereby improving the stability of the pressed powder under low temperature, high temperature and high and low temperature cycles and falling, and can form a thin protective film on the skin surface, which can better fix the plant extracts and phytic acid on the skin surface, improve the fit of the makeup, and improve the oil control and makeup retention. Furthermore, the inventors unexpectedly found that when the mass ratio of powder, plant extract, locust bean gum silane prepolymer and phytic acid is controlled to be (14-16): (1-2): (1.5-2.5): 1, the makeup effect of the pressed powder can be significantly improved, and the resulting pressed powder has better water resistance and stability.
[0040] Preferably, the film-forming agent is selected from at least one of trimethylsiloxysilicate, acrylates / polytrimethylsiloxane methacrylate copolymer, polyvinyl pyrrolidone-hexadecene copolymer, and polymethylsilsesquioxane, preferably trimethylsiloxysilicate.
[0041] Preferably, the emollient is selected from at least one of octyldodecyl stearoyloxystearate, cetyl dimethicone, squalane, and tocopherol acetate, preferably squalane.
[0042] The second aspect of the present invention provides a method for preparing the above-mentioned waterproof and non-sticky powder cake, comprising the following steps: mixing the powder and the plant extract at 2000-3000 rpm for 6-8 minutes to obtain a primary mixture; after the film-forming agent and the emollient are evenly mixed at 40-60°C, the locust bean gum silane prepolymer, phytic acid and the primary mixture are mixed at 3000-4000 rpm for 6-8 minutes to obtain a powder cake mixture, and the powder cake mixture is ground and pressed into shape after passing through a 100-mesh sieve.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] 1. The present invention creatively prepares silica hybrid corn starch, amino porous corn starch and stearic acid-tannic acid hybrid mica powder; by adopting the above technical scheme, the powder has good hydrophobicity and good water resistance, and at the same time has excellent oil control and makeup holding properties and matte soft focus properties even without using talcum powder; in addition, the powder resistance of the powder cake and the stability under high and low temperature cycles are also improved.
[0045] 2. Plant extracts are added to the system of the present invention. When the plant extract is a mixture of chicory root extract, phytosphingosine and Gynostemma pentaphyllum extract, it is mixed with powder, locust bean gum silane prepolymer and phytic acid. The components cooperate with each other to improve the fit of makeup while maintaining waterproofness, oil control and makeup holding, and avoid powder sticking.
[0046] 3. The present invention creatively uses 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane to modify locust bean gum. The modified locust bean gum has a higher adhesion to the powder and other ingredients, forming a more stable composite structure, which can reduce the possibility of cracking and falling off, thereby improving the stability of the powder under low temperature, high temperature, high and low temperature cycles and falling, and can form a thin protective film on the skin surface, which can better fix the plant extracts and phytic acid on the skin surface, improve the fit of the makeup, and improve the oil control and makeup retention.
[0047] 4. When the mass ratio of powder, plant extract, locust bean gum silane prepolymer and phytic acid is controlled to be (14-16): (1-2): (1.5-2.5): 1, the makeup effect of the powder can be significantly improved, and the obtained powder has better water resistance and stability. DETAILED DESCRIPTION
[0048] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, a specific implementation scheme is now described in detail.
[0049] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to the different requirements of specific use, and the implementation conditions not indicated are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0050] In the following examples and comparative examples, unless otherwise specified, the raw materials used are commercially available or prepared by conventional methods in the art. It should also be noted that the manufacturers of all plant extracts used in the examples of the present invention are only for illustrative purposes, and the source of the manufacturer does not affect the main active ingredients and the effects of the present invention.
[0051] Example 1
[0052] A waterproof and non-sticky pressed powder cake comprises, by weight, 30 parts of powder, 2 parts of plant extract, 4 parts of locust bean gum silane prepolymer, 3 parts of film former, 2 parts of emollient and 2 parts of phytic acid.
[0053] The powder is a mixture of silicon dioxide hybrid corn starch, amino porous corn starch and stearic acid-tannic acid hybrid mica powder; the mass ratio of the silicon dioxide hybrid corn starch, amino porous corn starch and stearic acid-tannic acid hybrid mica powder is 1:20:8.
[0054] The preparation method of the silicon dioxide hybrid corn starch is:
[0055] S1. dissolving waxy corn starch in phosphate buffer, stirring at 100° C. for 40 min to completely gelatinize it, and obtaining a starch solution; cooling the starch solution to 58° C., adding pullulanase for debranching for 8 h, centrifuging at 3500 rpm for 1 min after debranching, removing the precipitate, boiling the supernatant to inactivate the pullulanase, and centrifuging at 3500 rpm for 1 min to obtain a debranched starch solution; reversing the debranched starch solution at 50° C. for 10 h, and centrifuging at 3500 rpm for 10 min after reversing to obtain a precipitate; washing and drying the precipitate to obtain nano-resistant corn starch;
[0056] S2. Place nano-resistant corn starch in ethanol, add ethyl orthosilicate and water, and react at 80°C for 5 hours. During the reaction, add ammonia water to adjust the pH to 11. After the reaction, wash and dry the product.
[0057] The ratio of the waxy corn starch to the phosphate buffer is 1 g:10 mL.
[0058] The added amount of the pullulanase is 40u / g waxy corn starch.
[0059] Waxy corn starch was purchased from Shandong Fuyang Biotechnology Co., Ltd.
[0060] Phosphate buffer was purchased from Wuhan Pronocell Life Science Co., Ltd., catalog number PB180327.
[0061] Pullulanase was purchased from Shanghai Kanglang Biotechnology Co., Ltd.
[0062] Tetraethyl orthosilicate was purchased from Shandong Sike New Materials Co., Ltd.
[0063] The mass ratio of the nano-resistant corn starch, ethanol, tetraethyl orthosilicate and water is 1:70:6:4.
[0064] The preparation method of the aminated porous corn starch specifically comprises the following steps: placing the porous corn starch in an ethanol aqueous solution, adding γ-aminopropyltriethoxysilane to react at 75° C. for 8 hours, and filtering, washing and drying after the reaction is completed.
[0065] The mass ratio of the porous corn starch, the ethanol aqueous solution and γ-aminopropyltriethoxysilane is 1:6:0.1.
[0066] The ethanol aqueous solution is a mixture of ethanol and water in a mass ratio of 5:1.
[0067] Porous corn starch was purchased from Shaanxi Baichuan Biotechnology Co., Ltd.
[0068] γ-Aminopropyltriethoxysilane was purchased from Shandong Sike New Materials Co., Ltd.
[0069] The preparation method of the stearic acid-tannic acid hybrid mica powder is:
[0070] (1) placing tannic acid and mica powder in water at 80° C. for reaction for 2.5 hours, centrifuging, washing, and drying the tannic acid hybrid mica powder after the reaction is completed;
[0071] (2) Tannic acid hybrid mica powder, stearic acid and ethanol are mixed and reacted at 80° C. for 1.5 h. After the reaction is completed, the mixture is centrifuged, washed and dried to obtain the obtained product.
[0072] The mica powder has a D90 of 3 μm and is purchased from Shijiazhuang Chenxing Industrial Co., Ltd.
[0073] Tannic acid was purchased from Guiyang Beilong Chemical Co., Ltd.
[0074] Stearic acid was purchased from Hangzhou Zanyu Oil Technology Co., Ltd., model: SAI842.
[0075] The mass ratio of the tannic acid, mica powder and water is 10:1:100.
[0076] The mass ratio of the tannic acid hybrid mica powder, stearic acid and ethanol is 1:0.1:10.
[0077] The plant extract is a mixture of chicory root extract, phytosphingosine and Gynostemma pentaphyllum extract, and the mass ratio of the chicory root extract, phytosphingosine and Gynostemma pentaphyllum extract is 6:1:3.
[0078] Chicory root extract was purchased from Xi'an Virgin Biotechnology Co., Ltd. with a specification of 98% inulin.
[0079] Phytosphingosine was purchased from Shaanxi Chengqian Biotechnology Co., Ltd. with a specification of 98%.
[0080] Gynostemma pentaphyllum extract was purchased from Shaanxi Xiazhou Biotechnology Co., Ltd., item number XZ-DTYXCF-0019, specification 30:1.
[0081] The preparation method of the locust bean gum silane prepolymer comprises the following steps: placing locust bean gum in water, stirring at 80° C. for 30 minutes, adding potassium hydroxide, and dripping 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane into the water to react at 90° C. for 3 hours to obtain the prepolymer.
[0082] The mass ratio of the locust bean gum, water, potassium hydroxide and 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane is 10:20:0.2:4.
[0083] Locust bean gum was purchased from Dongguan Xinyao Biotechnology Co., Ltd.
[0084] 3-(1,3-Dimethylbutylene)aminopropyltriethoxysilane was purchased from Wuhan Jushun Chemical Co., Ltd.
[0085] The film-forming agent is trimethylsiloxysilicate, which was purchased from Guangzhou Lianzhuo Trading Co., Ltd.
[0086] The emollient is squalane, which was purchased from Wuhan Maikairui Chemical Co., Ltd.
[0087] The method for preparing the waterproof and non-sticky pressed powder comprises the following steps:
[0088] The powder and the plant extract are mixed at 2500 rpm for 6 minutes to obtain a primary mixture; the film former and the emollient are mixed evenly at 50° C., and then the locust bean gum silane prepolymer, phytic acid and the primary mixture are mixed at 3500 rpm for 6 minutes to obtain a powder mixture, and the powder mixture is ground and passed through a 100-mesh sieve and then pressed into a shape.
[0089] Example 2
[0090] The difference from Example 1 is that the waterproof and non-sticky powder cake consists of 60 parts of powder, 5 parts of plant extract, 8 parts of locust bean gum silane prepolymer, 6 parts of film-forming agent, 5 parts of emollient, and 4 parts of phytic acid as raw materials, calculated by mass; the rest are the same.
[0091] The preparation method of the waterproof and non-sticky pressed powder is the same as that of Example 1.
[0092] Example 3
[0093] The difference from Example 1 is that the waterproof and non-sticky powder cake consists of 45 parts of powder, 4 parts of plant extract, 6 parts of locust bean gum silane prepolymer, 5 parts of film-forming agent, 3 parts of emollient, and 3 parts of phytic acid as raw materials, calculated by mass; the rest are the same.
[0094] The preparation method of the waterproof and non-sticky pressed powder is the same as that of Example 1.
[0095] Comparative Example 1
[0096] The difference from Example 3 is that the silicon dioxide hybrid corn starch is replaced by talc / polydimethylsiloxane / triethoxyoctylsilane of equal mass, trade name: Talc FM DAS; the rest are the same.
[0097] Comparative Example 2
[0098] The difference from Example 3 is that the amino-modified porous corn starch is replaced with an equal mass of silicon dioxide hybrid corn starch; the rest are the same.
[0099] Comparative Example 3
[0100] The difference from Example 3 is that the stearic acid-tannic acid hybrid mica powder is replaced by mica / polydimethylsiloxane / triethoxyoctylsilane of equal mass, trade name: UNI-Sericite 2500DAS; the rest are the same.
[0101] Comparative Example 4
[0102] The difference from Example 3 is that the locust bean gum silane prepolymer is replaced with locust bean gum of the same mass; the rest are the same.
[0103] Comparative Example 5
[0104] The difference from Example 3 is that the plant extract is replaced by three raw materials in the plant extract disclosed in the prior art CN 116712377 A, that is, the plant extract is Centellin extract, Imperata cylindrica (L.) Beauv. root extract and Sargassum extract; the mass ratio of the Centellin extract, Imperata cylindrica (L.) Beauv. root extract and Sargassum extract is 1:1:1; the rest are the same.
[0105] Centella asiatica extract was purchased from Xi'an Green Sky Biotechnology Co., Ltd., product code PMQD0802; Imperata cylindrica root extract was purchased from Shaanxi Shengheyuan Biotechnology Co., Ltd., specification 10:1; Sargassum extract was purchased from Xi'an Shangcheng Biotechnology Co., Ltd., specification 10:1.
[0106] Comparative Example 6
[0107] The difference from Example 3 is that the mass ratio of powder, plant extract, locust bean gum silane prepolymer and phytic acid is 12:0.5:1:1, that is, the waterproof and non-sticky powder cake consists of 48 parts of powder, 2 parts of plant extract, 4 parts of locust bean gum silane prepolymer, 5 parts of film-forming agent, 3 parts of emollient and 4 parts of phytic acid; the rest are the same.
[0108] Performance Test:
[0109] The waterproof and non-sticky pressed powders of Examples 1-3 and Comparative Examples 1-6 were subjected to the following performance tests:
[0110] 1. Waterproofness: (1) Soak the powder cake in 25°C water for 48 hours to obtain the soaked sample, and visually inspect whether the sample absorbs water and breaks; (2) Use an optical contact angle meter to measure the contact angle between the powder cake surface and water. The results are shown in Table 1;
[0111] 2. Skin feel: 90 healthy female volunteers aged 20-40 were selected, and the skin quality of the selected volunteers was oily skin or mixed skin quality. The subjects were randomly divided into 10 groups, with 10 people in each group; the skin feel of the powder cakes of Examples 1-3 and Comparative Examples 1-6 was tested respectively, and each subject applied the same amount of powder cake on the left and right faces respectively. The subjects evaluated the application process and the effect after application (after 6 hours), and the evaluation indexes and scoring criteria were as follows:
[0112] (1) Skin adhesion refers to the degree to which makeup remains intact after application: 1 point: not sticking to the skin, severe powder sticking; 2 points: not sticking to the skin, obvious powder sticking; 3 points: average skin adhesion; 4 points: good skin adhesion, almost no powder sticking; 5 points: good skin adhesion, no powder sticking at all;
[0113] (2) Matte soft focus refers to the ability of the product to conceal skin imperfections after use: 1 point: poor, pores are prominent; 2 points: relatively poor, pores are not concealed; 3 points: fair, some pores are concealed; 4 points: relatively good, most pores are concealed; 5 points: good, all pores are concealed.
[0114] (3) Oil control and makeup lastingness refers to the ability of makeup to resist sweat and oil after use: 1 point: poor; 2 points: relatively poor; 3 points: average; 4 points: relatively good; 5 points: good.
[0115] (4) Powder flying degree refers to the degree of powder flying during use: 1 Very bad, a lot of powder flying; 2 Poor, powder flying; 3 Average, a little powder flying; 4 Good, not much powder flying; 5 Very good, no powder flying
[0116] (5) Makeup effect preference refers to the overall evaluation of the product after use: 1 point: poor; 2 points: poor; 3 points: average; 4 points: good; 5 points: good.
[0117] The testers scored according to the above scoring criteria, and finally all the scores were counted and the average value was calculated. The results are shown in Table 2.
[0118] 3. Stability test:
[0119] (1) The powder is subjected to accelerated testing at -5°C, 40°C, and 45°C for three months, and to a -5-40°C hot and cold cycle for one week. After returning to room temperature, the powder remains unchanged and can be used normally. This is considered qualified. If the powder cracks, falls off, or cannot be used normally, it is considered unqualified.
[0120] (2) Drop test: The powder cake is dropped from a height of 50 cm onto a 2.5 cm thick wooden board. If the number of powder breakages is ≤1, it is considered qualified; otherwise, it is considered unqualified. The results are shown in Table 3.
[0121] Table 1 Waterproof test results of the waterproof and non-sticky powder cakes of Examples 1-3 and Comparative Examples 1-6
[0122] Appearance of powder after soaking Contact angle / ° Example 1 No water absorption, no breakage 145 Example 2 No water absorption, no breakage 146 Example 3 No water absorption, no breakage 148 Comparative Example 1 No water absorption, no breakage 158 Comparative Example 2 Partially absorb water, partially crushed 136 Comparative Example 3 No water absorption, no breakage 155 Comparative Example 4 Partially absorb water, partially crushed 140 Comparative Example 5 No water absorption, no breakage 145 Comparative Example 6 Partially absorb water, partially crushed 150
[0123] Table 2 Skin feel test results of waterproof and non-sticky powder cakes of Examples 1-3 and Comparative Examples 1-6
[0124] Skin-friendly makeup Matte Soft Focus Oil control and makeup lasting Powder extraction powder Makeup effect preference Example 1 4.6 4.7 4.6 4.6 4.6 Example 2 4.8 4.8 4.8 4.5 4.6 Example 3 4.9 4.8 4.9 4.8 4.8 Comparative Example 1 3.6 4.1 4.6 3.7 3.8 Comparative Example 2 4.1 3.8 3.7 3.2 3.5 Comparative Example 3 3.8 3.6 4.3 3.4 3.6 Comparative Example 4 3.8 4.1 4.1 3.5 3.8 Comparative Example 5 3.5 3.7 3.6 3.7 3.7 Comparative Example 6 3.6 3.8 3.9 4.1 3.3
[0125] Table 3 Stability test results of waterproof and non-sticky powder cakes of Examples 1-3 and Comparative Examples 1-6 It can be seen from Tables 1 to 3 that the waterproof and non-sticky pressed powder of Examples 1 to 3 has good water resistance, skin feel and stability;
[0126] In Comparative Example 1, the silica hybrid corn starch was replaced with talc / polydimethylsiloxane / triethoxyoctylsilane of equal mass; although the obtained powder cake had good waterproofness, the skin adhesion and powder fly-off degree were reduced, and it failed in the hot and cold cycle and drop tests;
[0127] In Comparative Example 2, the amino porous corn starch was replaced with the silica hybrid corn starch of the same mass, and the obtained pressed powder had decreased water resistance, decreased powder flyaway, decreased makeup effect, and unqualified cold and hot cycle stability at -5°C;
[0128] Comparative Example 3: Stearic acid-tannic acid hybrid mica powder was replaced with mica / polydimethylsiloxane / triethoxyoctylsilane of the same mass. Although the obtained pressed powder had good water resistance, the matte soft focus, powder flyaway and makeup effect liking were reduced, and the stability at 45°C was unqualified.
[0129] In Comparative Example 4, locust bean gum silane prepolymer was replaced with locust bean gum of equal mass, and the obtained powder cake had decreased water resistance and powder fly ash degree, and failed to meet the standards in stability at -5°C, 45°C, hot and cold cycle, and drop test.
[0130] In Comparative Example 5, the plant extracts were replaced with the three plant extracts disclosed in the prior art CN 116712377 A; the waterproofness and stability of the obtained powder cake remained unchanged, but the skin adhesion and oil control and makeup lastingness decreased;
[0131] In Comparative Example 6, the mass ratio of powder, plant extract, locust bean gum silane prepolymer and phytic acid is not in the range of (14-16): (2-4): (1.5-2.5): 1; the waterproofness of the obtained powder cake is reduced, the degree of skin adhesion and the degree of makeup effect are reduced, and the stability at -5°C and the drop test are unqualified.
[0132] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A waterproof and non-sticky pressed powder, characterized in that: The raw materials include 30-60 parts of powder, 2-5 parts of plant extract, 4-8 parts of locust bean gum silane prepolymer, 3-6 parts of film former, 2-5 parts of emollient, and 2-4 parts of phytic acid by weight; The powder is a mixture of silicon dioxide hybrid corn starch, amino porous corn starch and stearic acid-tannic acid hybrid mica powder; The mass ratio of the silicon dioxide hybrid corn starch, the amino porous corn starch and the stearic acid-tannic acid hybrid mica powder is 1:(10-25):(5-10).
2. The waterproof and non-sticky pressed powder according to claim 1, characterized in that: The method for preparing the silicon dioxide hybrid corn starch comprises the following steps: S1. dissolving waxy corn starch in a phosphate buffer, heating and stirring to completely gelatinize the starch to obtain a starch solution; cooling the starch solution, adding pullulanase to debranch the starch solution, centrifuging the solution after debranching, removing the precipitate, boiling the supernatant to inactivate the pullulanase, and centrifuging the solution again to obtain a debranched starch solution; retrograding the debranched starch solution, centrifuging the solution after retrogradation to obtain a precipitate; washing and drying the precipitate to obtain nano-resistant corn starch; S2. Place nano-resistant corn starch in ethanol, add tetraethyl orthosilicate and water to react, add ammonia water dropwise during the reaction to adjust the pH to 10.5-11.5, and wash and dry the product after the reaction.
3. The waterproof and non-sticky pressed powder according to claim 2, characterized in that: The preparation method of the aminated porous corn starch comprises the following steps: placing the porous corn starch in an ethanol aqueous solution, adding gamma-aminopropyltriethoxysilane to react, and filtering, washing and drying after the reaction is completed.
4. The waterproof and non-sticky pressed powder according to claim 3, characterized in that: The preparation method of the stearic acid-tannic acid hybrid mica powder comprises the following steps: (1) placing tannic acid and mica powder in water for reaction, and after the reaction is completed, centrifuging, washing, and drying to obtain tannic acid hybrid mica powder; (2) Mix tannic acid hybrid mica powder, stearic acid and ethanol to react, and after the reaction is completed, centrifuge, wash and dry to obtain the product.
5. The waterproof and non-sticky pressed powder according to claim 4, characterized in that: The plant extract is a mixture of chicory root extract, phytosphingosine and Gynostemma pentaphyllum extract, and the mass ratio of the chicory root extract, phytosphingosine and Gynostemma pentaphyllum extract is (4-8):1:(2-4).
6. The waterproof and non-sticky pressed powder according to claim 5, characterized in that: The preparation method of the locust bean gum silane prepolymer comprises the following steps: placing locust bean gum in water, stirring, adding potassium hydroxide, and dripping 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane to react to obtain the prepolymer.
7. The waterproof and non-sticky pressed powder according to claim 6, characterized in that: The mass ratio of the powder, the plant extract, the locust bean gum silane prepolymer and the phytic acid is (14-16): (1-2): (1.5-2.5):
1.
8. The waterproof and non-sticky pressed powder according to claim 7, characterized in that: The film-forming agent is selected from at least one of trimethylsiloxysilicate, acrylate / polytrimethylsiloxane methacrylate copolymer, polyvinyl pyrrolidone-hexadecene copolymer, and polymethylsilsesquioxane.
9. The waterproof and non-sticky pressed powder according to claim 8, characterized in that: The emollient is selected from at least one of octyldodecyl stearyloxystearate, cetyl dimethicone, squalane, and tocopherol acetate.
10. The method for preparing the waterproof and non-sticky pressed powder according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing powder and plant extract at 2000-3000 rpm for 6-8 minutes to obtain a primary mixture; mixing a film former and an emollient at 40-60° C. evenly, mixing locust bean gum silane prepolymer, phytic acid and the primary mixture at 3000-4000 rpm for 6-8 minutes to obtain a powder mixture, grinding the powder mixture, passing it through a 100-mesh sieve, and pressing and molding the mixture.
Citation Information
Patent Citations
A waterproof, sweat-proof, long-lasting, skin-nourishing powder compact and its preparation method
CN115363967B